Temperature compensated low voltage MOSFET radiation sensor: proof of concept and a case study - Pablo Petrashin; Walter Lancioni; Luis Toledo; Agustin Laprovitta; Juan Castagnola (Department of Electrical Engineering ITS and FORTEI, 2020)
This paper presents a proof of concept performed on a new and very simple CMOS circuit configuration that implements a radiation dosimeter based on the threshold voltage difference (VTH) principle. The circuit used does not use resistors and all the transistors work in strong inversion, their mobility factor being completely canceled by the proposed architecture. Its operation exploits the relationship between radiation and VTH shifting, which allows, through a circuit configuration, to compensate for temperature variation and amplify the reaction to radiation, making it ideal for integrated industrial applications due to its simplicity and good operation. The circuit was designed for operation in areas naturally at risk of radiation, for example nuclear power plants or radiological clinics. Its advantage over other circuits that perform similar functions is mainly its low cost and simplicity of design.Keywords: CMOS dosimeters, radiation dosimetry, temperature compensation.